2018
DOI: 10.1063/1.4998793
|View full text |Cite
|
Sign up to set email alerts
|

Pedestals and feedback in fusion-plasma relevant sandpile models

Abstract: We present modifications to the sandpile model [Chapman, Phys. Rev. E 62, 1905 (2000)] (Classic Model). A feedback loop is added to the Classic Model, elements of which may have relevance to the behaviour of a fusion plasma. Those elements include variation of the total energy of the system in proportion to a proxy for the Larmor radius, ρ, and resulting variations in mass loss event (MLE) size and waiting times between MLEs. We also show other variants of the Classic Model which produce pedestals, without int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…An aspect of pellet pacing in fusion plasmas which is not captured in our model is that pellets for ELM mitigation are typically added at the top of the pedestal -pellets injected into the core are typically used for fuelling rather than pellet pacing. In future work, we propose to adapt a version of the sandpile model which incorporates a pedestal [26] to determine whether that will produce a better comparison with experimental results. Longer term, the extension to a 2D sandpile offers the possibility of capturing the radial-varying poloidal and toroidal twist of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…An aspect of pellet pacing in fusion plasmas which is not captured in our model is that pellets for ELM mitigation are typically added at the top of the pedestal -pellets injected into the core are typically used for fuelling rather than pellet pacing. In future work, we propose to adapt a version of the sandpile model which incorporates a pedestal [26] to determine whether that will produce a better comparison with experimental results. Longer term, the extension to a 2D sandpile offers the possibility of capturing the radial-varying poloidal and toroidal twist of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…The median waiting time, ∆t n , between MLEs is ∼135000, and ∆S max is ∼630000. The energy of the system [32]. For the sandpile chosen, the width of the pedestal, P w , is ∼15/500 cells, meaning that the top of the pedestal is located at n = 485.…”
Section: Dual-fuelled Sandpilementioning
confidence: 99%
“…The resulting pedestal was introduced as a proxy for the pedestal of a fusion plasma in a H-mode plasma [32]. The feedback loops were seen to be analagous to the feedback effects intrinsic to the H-mode pedestal in a fusion plasma [32]. It was suggested that reduction of feedback in the pedestal could result in ELM suppression within a H-mode plasma [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is shown that the model has an analytic solution when the fuelling rate is high enough to satisfy two necessary conditions, both of which are identified here. Motivated by pellet injection systems in fusion plasmas, both the original sandpile model, and the modified versions developed here, are then employed to test whether adding 'pellets' of sand to the sandpile can reduce the size 2 C. Bowie [2] of the largest avalanches. Pellets of sand added at the core in the original model are found not to be effective in reducing the size of the largest avalanches.…”
mentioning
confidence: 99%